Trustworthy AI and Trust in Audit: between Prudence and Reputational Risks - Cătălin Paul PĂCURARU-IONESCU; Răzvan HOINARU (Revista de Management Comparat International)
In this article the authors explore the matching between the theory and practice of trust in audit and trustworthiness of Artificial Intelligence (AI). While AI does not have a theory of its own, it is an instrument that contributes to theory testing and has conceptual lenses of its own. The currently existing narrow AI has its limits in connecting to audit services. Document processing, data collection and structuring are among the possible functions, however, human supervision is needed as much as professional judgement. The effects of using AI in auditing practice are not clear yet and how reputational risk and independence are affected will be explored. Also, uncertainty dominates the cost benefits analysis in using AI powered technology and services in audits. There is a supply and demand of services in audit and advancements that go hand in hand with regulation of safety, consumer protection and sustainability. Both AI behaviour and audit practice are a matter of socially constructed functions where peer to peer review plays a great role in markets in terms of reputational risks and independence.